A Novel Affinity Engineered Anti-CD47 Antibody With Improved Therapeutic Index That Preserves Erythrocytes and Normal Immune Cells - Thaker, Youg R.; Rivera, Ianne; Pedros, Christophe; Singh, Alok R.; Rivero-Nava, Laura; Zhou, Heyue; Swanson, Barbara A.; Kerwin, Lisa; Zhang, Yanliang; Gray, J. Dixon; Kaufmann, Gunnar F.; Ji, Henry; et al. (Frontiers in Oncology, 2022)
Therapeutic blockade of the CD47/SIRPα axis by small molecules or monoclonal antibodies (mAbs) is a proven strategy to enhance macrophages-mediated anti-tumor activity. However, this strategy has been hampered by elevated on-target toxicities and rapid clearance due to the extensive CD47 expression on normal cells (“antigen sink”) such as red blood cells (RBCs). To address these hurdles, we report on the development of STI-6643, an affinity-engineered fully human anti-CD47 IgG4 antibody with negligible binding to normal cells. STI-6643 exhibited no hemagglutination activity on human RBCs at concentrations up to 300 µg/mL yet specifically blocked the CD47/SIPRα interaction. Of particular interest, STI-6643 preserved T cell functionality in vitro and showed significantly lower immune cell depletion in vivo in contrast to three previously published competitor reference anti-CD47 clones Hu5F9, AO-176 and 13H3. In cynomolgus monkeys, STI-6643 was well-tolerated at the highest dose tested (300 mg/kg/week) and provided favorable clinical safety margins. Finally, STI-6643 displayed comparable anti-tumor activity to the high-affinity reference clone Hu5F9 in a RAJI-Fluc xenograft tumor model as monotherapy or in combination with anti-CD20 (rituximab) or anti-CD38 (daratumumab) mAbs. These data suggest that STI-6643 possesses the characteristics of an effective therapeutic candidate given its potent anti-tumor activity and low toxicity profile.